A Review of Current Challenges, Influential Factors, and Advancements in Goat Semen Cryopreservation - , Amit Kumar; , Kanaka KK; , Himanshu Mehta; , Navjot Singh Thakur; , Gyan Singh (Archives of Current Research International, 2025)
Goat semen cryopreservation plays a crucial role in the management and improvement of breeding programs, but it is accompanied by numerous challenges that hinder its success. The high cryo-sensitivity of goat sperm, particularly due to their lipid-rich membranes, makes them susceptible to damage during freezing and thawing processes. Additionally, the composition of seminal plasma, seasonal variations, and breed-specific differences further complicate semen preservation. This review highlights the key factors that influence the cryopreservation of goat semen, including the role of cryoprotectants, antioxidants, and the freezing-thawing protocols. Advances in techniques such as vitrification, freeze-drying, and the use of nanotechnology are discussed, as they offer promising solutions to improve post-thaw sperm quality. Furthermore, the application of bio- stimulants and novel extenders has shown potential in enhancing sperm survival and functionality. Despite the progress made, further improvements are necessary to address issues such as oxidative stress, cryodamage, and environmental factors. By addressing the challenges and limitations in the existing preservation methods, this article seeks to provide valuable insights for researchers, practitioners, and the broader livestock industry involved in goat breeding and reproduction.